2005
DOI: 10.1111/j.1440-1746.2005.04013.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal: Inflammatory myoglandular polyp of the colon

Abstract: An inflammatory myoglandular polyp of the large bowel is a rare but distinct clinical entity that was first described by Dr S Nakamura and others in 1992. It is characterized histologically by inflammatory granulation tissue in the lamina propria, proliferation of smooth muscle and hyperplastic glands which sometimes show cystic dilatation. The typical endoscopic appearance is that of a pedunculated spherical polyp with a smooth surface and patchy redness that resembles a ripe strawberry. There may also be a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…According to Fujino et al [8] , a review of the literature revealed 48 cases of IMGP in the large intestine up to 2001. However, recent advances in diagnostic techniques have enabled us to identify small and asymptomatic polyps, and reports on IMGP of the colon have been increasing [9,10] . Fujino et al [8] described that the macroscopic appearance was the pedunculated type in 83.3% of cases.…”
Section: A1 B C A2mentioning
confidence: 99%
See 4 more Smart Citations
“…According to Fujino et al [8] , a review of the literature revealed 48 cases of IMGP in the large intestine up to 2001. However, recent advances in diagnostic techniques have enabled us to identify small and asymptomatic polyps, and reports on IMGP of the colon have been increasing [9,10] . Fujino et al [8] described that the macroscopic appearance was the pedunculated type in 83.3% of cases.…”
Section: A1 B C A2mentioning
confidence: 99%
“…Endoscopic characteristic findings are as follows: (1) pedunculated or semipedunculated, (2) red and (3) smooth, spherical and hyperemic surface with patchy mucous exudation and erosion [8,9] . IMGPs should be distinguished from other colorectal polyps such as inflammatory fibroid polyps (IFP) [10,13] , Peutz-Jeghertype polyps or juvenile polyps [10,11] . However, the correct endoscopic diagnosis of colorectal IMGP can seldom be made.…”
Section: A1 B C A2mentioning
confidence: 99%
See 3 more Smart Citations